Dipicrylhydrazine: A versatile visual anions sensor. Issue 3 (June 2017) - Sharma, Pragati R.; Soni, Vineet Kumar; Pandey, Shubham; Choudhary, Ganpat; Plappally, Anand K.; Sharma, Rakesh K.
Graphical abstract: Dipicrylhydrazineis proposed as a simple and effective visual sensor for F −, CN −, OH −, CH3 COO − and HSO4 − anions. Highlights: We developed new visual anion sensor based on dipicrylhydrazine. The new sensor gave sharp color change for fluoride, cyanide, acetate, hydrogen sulphate and hydroxide anions. The time dependent NMR study revealed stronger interaction for cyanide and fluoride ions among competing anions. Abstract: The current study involves a simple hydrazine based colorimetric chemo-sensor for selective determination of various anions. The anion-binding ability of the ligand with various anions via polar-non polar interactions and hydrogen bonding has been examined. The sensor displayed significant UV–vis enhancement response to anions such as fluoride, acetate, hydroxide, cyanide and hydrogen sulphate, with respect to concentration and time. The rate constants ( K ) and binding constants, Ka, for these anions have been measured by using Benesi-Hildebrand equation. A time dependent NMR study revealed stronger interaction for cyanide and fluoride ions among competing anions.